Effective computation of base points of ideals in two-dimensional local rings. (May 2019) - Alberich-Carramiñana, Maria; Àlvarez Montaner, Josep; Blanco, Guillem
Abstract: We provide an algorithm that allows to describe the minimal log-resolution of an ideal in a smooth complex surface from the minimal log-resolution of its generators. In order to make this algorithm effective we present a modified version of the Newton–Puiseux algorithm that computes the Puiseux decomposition of a product of not necessarily reduced or irreducible elements together with their algebraic multiplicity in each factor.